2018
DOI: 10.1007/s10047-018-1056-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis using the prognostic nutritional index in hemodialysis-dependent patients undergoing cardiac surgery

Abstract: The prognostic nutritional index is an effective prognostic tool used in gastrointestinal surgeries. However, its value has not been verified in cardiovascular surgeries. This study aimed to investigate its utility in hemodialysis-dependent patients undergoing cardiac surgery. We retrospectively reviewed data of 110 hemodialysis-dependent patients who underwent cardiac surgery between January 2006 and July 2016. 20 variables were evaluated for short- and long-term mortality prediction. Patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
0
14
0
5
Order By: Relevance
“…In 1984, Onodera simplified the linear predictive model using immune-nutritional indicators according to the following equation: PNI = SA (g/L) + (5 × total lymphocyte count [TLC] × 10 9 /L). This study showed that the model could be used safely when PNI was over 45 9 , but some reports showed that the optimal cut-off value of PNI is variable 10,11 . PNI was used to prognosticate various malignancies 12–16 , pulmonary embolism 17 , and other diseases.…”
Section: Introductionmentioning
confidence: 83%
“…In 1984, Onodera simplified the linear predictive model using immune-nutritional indicators according to the following equation: PNI = SA (g/L) + (5 × total lymphocyte count [TLC] × 10 9 /L). This study showed that the model could be used safely when PNI was over 45 9 , but some reports showed that the optimal cut-off value of PNI is variable 10,11 . PNI was used to prognosticate various malignancies 12–16 , pulmonary embolism 17 , and other diseases.…”
Section: Introductionmentioning
confidence: 83%
“…PNI score, which has a better predictive value than albumin levels alone, is primarily used in the follow-up of patients with gastrointestinal malignancies, over the time it has been introduced as a prognostic predictor for many chronic diseases, especially for cardiovascular diseases. 17,21,28,32,33 Previously, Lee et al 34 reported that 374 patients who underwent coronary artery bypass surgery, PNI score ≤ 46.1 was found significantly higher short-term adverse events including morbidity, mortality, and ICU stay. 32 In 2019, Okuno et al 32 indicated that low PNI scores were a significant predictor of long-term mortality in patients undergoing TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of our study, the all‐cause mortality rate after SAVR appears to be higher in patients with low albumin levels. PNI score, which has a better predictive value than albumin levels alone, is primarily used in the follow‐up of patients with gastrointestinal malignancies, over the time it has been introduced as a prognostic predictor for many chronic diseases, especially for cardiovascular diseases 17,21,28,32,33 . Previously, Lee et al 34 reported that 374 patients who underwent coronary artery bypass surgery, PNI score ≤ 46.1 was found significantly higher short‐term adverse events including morbidity, mortality, and ICU stay 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, our results indicated that patients with poor PNI value would have a high risk of post-operation complications which would shorten the OS time of the cancer patients. Moreover, poor nutritional and immune status could make cancer patients unable to tolerate post-operative adjuvant therapy (41). As a consequence, patients abandon post-operative adjuvant therapy, which shorten the survival time and make patients have a poor quality of life.…”
Section: Discussionmentioning
confidence: 99%